1979
DOI: 10.1152/jappl.1979.46.2.361
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of regional phase differences in ventilation by breath sounds

Abstract: We measured phase and amplitude of compensated breath sounds (Ib/Tn), which are indexes of regional ventilation, with two microphones placed near the apex and base 10 cm apart on the chest wall, lateral to the right anterior axillary line in four seated normal subjects. We compared phase and amplitude of Ib/Tn with phase and amplitude of esophageal pressure changes (Pes) measured by two balloons positioned 10 cm apart and at approximately the same horizontal levels as the microphones. When breathing tidally be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

1982
1982
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
0
13
0
3
Order By: Relevance
“…Many aspects of the sounds have been investigated such as: the sites of production [5], the power spectra [4,[6][7][8], the relationship with regional ventilation [3,9,10]. In terestingly, in all of these studies the issue of repro ducibility of the vesicular breath sounds and the var iation of these sounds among normal subjects have never been directly addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many aspects of the sounds have been investigated such as: the sites of production [5], the power spectra [4,[6][7][8], the relationship with regional ventilation [3,9,10]. In terestingly, in all of these studies the issue of repro ducibility of the vesicular breath sounds and the var iation of these sounds among normal subjects have never been directly addressed.…”
Section: Discussionmentioning
confidence: 99%
“…These are: ambient noise such as conversations, equipment noise, etc., skin and hair noise, muscle noise [4] and the heart sounds. By careful recording in a quiet or sound-proof room, by shaving the area where the microphone is placed, by a firm and good application of the microphone to the skin surface and by avoiding the recording at the extreme lung vol umes, i.e., near total lung capacity or residual volume [4,9], one can satisfactorily avoid all the above-men tioned extraneous noises except the heart sounds. The heart sounds are an inherent interference in lung sound analysis, for the simple fact that the heart can not be made to cease beating.…”
Section: Discussionmentioning
confidence: 99%
“…in addition, several reports provided evidence that breathsound amplitude is proportional to ventilation. For example, radionuclide labelled air studies (LEBLANC et al, 1970;PLOYSONGSANG et al, 1977;1978) concluded that lung sounds are loudest at the best ventilated lung regions. Furthermore, physical-examination findings in subjects with partial airway stenosis suggested diminished breath sounds over the lung supplied by the affected airway (JONES, 1988).…”
Section: Some Related Breath-sound Characteristicsmentioning
confidence: 99%
“…The inspiratory vesicular breath sound is characterized by a loud signal lasting throughout the inspiratory phase of respiratory cycle. Its production has been attri buted to airflow in the alveoli [1], the larynx [2,3], or the airways in between [4], More recent studies sug gest that the inspiratory component is produced within the lung near the auscultated area [5][6][7], Its fre quency spectrum has also been fairly well character ized and found to range from 75 to 500 Hz if high-pass filtered at 75-200 Hz [4,[8][9][10][11]. Urquhart et al [12] did not filter their recorded lungs sounds and found the peak power spectrum to range from 5 to 50 Hz.…”
Section: Introductionmentioning
confidence: 99%